MAUSU’AH WA MAFHUMUL HADIS LARANGAN TRANSAKSI RIBA DALAM MUSNAD AHMAD - Nur Hadi (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
AbstractIslam is a comprehensive religion that encapsulates all human life including economic activities. This era of modern and sophisticated times, the phenomenon of the development of existing business activities must be vigilant, so as not to fall prey to usury. Then what about the hadith in Ahmad's musnad relating to usury ?. The results of the author's research in the book mausu'ah al-hadis al-Nabawiyah, from the hadith perspective in the book Musnad Ahmad. Then found 6 traditions related to usury property. The hadith is No. Hadith 803 in the Book: Musnad of ten companions guaranteed to enter heaven, Chapter: Musnad Ali bin Abu Talib Radliyallahu 'anhu. Hadith No. 1222 in the Book: Musnad of ten companions who are guaranteed to enter heaven, Chapter: Musnad Ali bin Abu Talib Radliyallahu 'anhu. Hadith No. 1294 in the Book: Musnad of ten companions guaranteed to enter heaven, Chapter: Musnad Ali bin Abu Talib Radliyallahu 'anhu. Hadith No. 3539 in the Book: Musnad companions who have narrated many hadith, Chapter: Musnad Abdullah bin Mas'ud Radliyallahu ta'ala 'anhu. Hadith No. 3567 in the Book: Musnad friends who have narrated many hadith, Chapter: Musnad Abdullah bin Mas'ud Radliyallahu ta'ala 'anhu. Hadith No. 13744 in Ahmad Musnad, it will appear in the Book: Remaining Musnad companions who have narrated many hadith, Chapter: Musnad Jabir bin Abdullah Radliallahu ta'ala 'anhu. So from the hadith it can be drawn the understanding that Allah cursed the eaters of usury, the person who gave food with usury, the witness of the usury contract and the person who wrote it. Even though a lot of usury will eventually be a little.Keywords: Mausu'ah, Mafhum, Hadits, Prohibitions, Riba Transactions.